The interior design of Malaysian and Indonesian traditional mosque : comparative studies / Azizul Azli Ahmad and Jazmin Zulkifli - Azli, Azizul; Zulkifli, Jazmin (2018)
Nusantara Mosque has its own classification from the perspective of building a mosque architecture in the Islamic world. The Great Mosque of Demak is the oldest mosque in Alam Nusantara and is a reference to the construction of the mosque in the 18th Century and later. The relationship between the Indonesian and Malaysian societies has sparked the equation of the construction technology of the mosque and the design of mosques in both countries. This writing is intended to analyze the design and design of mosque interior space in Indonesia and Malaysia. This comparison study examines the differences and similarities found in the Great Mosque of Demak, Java and Kampung Hulu Mosque of Malacca as the object of study. Although these two samples are within the same scope but there is a disparity between the mosque developed in Indonesia and in Malaysia. This distinction becomes wider when Indonesia and Malaysia achieve independence. Islamic architecture Mosque of Nusantara managed to break out of Arab culture and give birth to its own art and style of art. It enriches the style of Islamic architecture and demonstrates tolerance in Islam that is so clear through the language of its art